2021
DOI: 10.1097/fjc.0000000000001010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Levosimendan on Ventricular Systolic and Diastolic Functions in Heart Failure Patients: A Meta-Analysis of Randomized Controlled Trials

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Although the echocardiographic data and hemodynamic effects of levosimendan have been previously shown in patients with acute HF hospitalized and treated in acute cardiac settings (see recent meta-analysis by Long et al 12 ), the same has not previously been demonstrated for patients with advanced HF who are not in acute hemodynamic imbalance.…”
Section: Discussionmentioning
confidence: 92%
“…Although the echocardiographic data and hemodynamic effects of levosimendan have been previously shown in patients with acute HF hospitalized and treated in acute cardiac settings (see recent meta-analysis by Long et al 12 ), the same has not previously been demonstrated for patients with advanced HF who are not in acute hemodynamic imbalance.…”
Section: Discussionmentioning
confidence: 92%
“…Levosimendan, a commonly used positive inotropic drug in heart failure, has been shown in previous meta-analyses to significantly improve ventricular systolic and diastolic function in patients with heart failure. [111][112][113] It is still unclear whether levosimendan treatment has an impact on ventricular remodelling. Various indicators can be used to assess ventricular remodelling, 114 such as cardiac size, shape, mass, and end-diastolic and end-systolic volumes.…”
Section: Discussionmentioning
confidence: 99%
“…In the patients with decompensated status requiring inotropes or intravenous diuretics, levosimendan may improve diastolic and systolic functions of both ventricles, but the benefits of hard endpoints, including hospitalizations and mortality, are contradictory [ 25 , 26 ]. In a randomized study on CV surgery, there was the trend of better outcomes upon use of levosimendan as compared to placebo use; however, significantly better outcomes were observed only in the subgroup of patients who underwent isolated coronary artery bypass graft surgery [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the patients with decompensated status requiring inotropes or intravenous diuretics, levosimendan may improve diastolic and systolic functions of both ventricles, but the benefits of hard endpoints, including hospitalizations and mortality, are contradictory [25,26].…”
Section: Levosimendan For Adhfmentioning
confidence: 99%